Analisis Karakteristik Breakdown Voltage Pada Dielektrik Minyak Transformator 45 MVA Dengan Suhu Operasi Yang Bervariasi Di Pusat Listrik Kota Panjang - Saribu, Daniel Harjono Dolok; Firdaus, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Breakdown voltage is a phenomenon when the voltage is constantly raised in isolation, the atoms will be ionized and to limit the ability of the insulation to withstand the voltage then the insulator will be the conductor. This critical moment is called breakdown. Voltage breakdown testing is required to determine the critical point of the insulating oil, in other words to determine the boundaries of oil withstand voltage exposure. The purpose of this research is to know the dielectric strength of the transformer oil power with temperature changes in the oil, temperature is known based on the temperature of the peak loads, the load average and the lowest load on the transformer that is in the electrical center of the Kota Panjang, the temperature of the oil to be tested is 50°C, 65°C dan 82°C, testing is done using high voltage AC, using the hemispherical electrode, gap 2,5 mm. Tests done 3 times per sample in a single state in the oil temperature. From the test results showed that the dielectric strength of the oil shell diala type b will increase as the temperature rise in transformer oil, and test 80°C in other words, the temperature of the oil is directly proportional to the dielectric strength.Keywords : Insulating temperature, breakdown voltage, dielectric strenght.